On ideal convergence of triple sequences in intuitionistic Fuzzy normed space defined by compact operator - Khan,Vakeel A. (Universidad Católica del Norte, Departamento de Matemáticas, 2021)
Abstract The main purpose of this article is to introduce and study some new spaces of I-convergence of triple sequences in intuitionistic fuzzy normed space defined by compact operator i.e 3SI (μ,ν)(T ) and 3SI 0(μ,ν)(T ) and examine some fundamental properties, fuzzy topology and verify inclusion relations lying under these spaces.